Poor sleep accelerates hippocampal and posterior cingulate volume loss in cognitively normal healthy older adults. (19th December 2021) - Liu, Che; Lee, Sang H.; Loewenstein, David A.; Galvin, James E.; Camargo, Christian J.; Alperin, Noam
Summary: Poor sleep quality is a known risk factor for Alzheimer's disease. This longitudinal imaging study aimed to determine the acceleration in the rates of tissue loss in cognitively critical brain regions due to poor sleep in healthy elderly individuals. Cognitively‐normal healthy individuals, aged ≥60 years, reported Pittsburgh Sleep Quality Index (PSQI) and underwent baseline and 2‐year follow‐up magnetic resonance imaging brain scans. The links between self‐reported sleep quality, rates of tissue loss in cognitively‐critical brain regions, and white matter hyperintensity load were assessed. A total of 48 subjects were classified into normal ( n = 23; PSQI score <5) and poor sleepers ( n = 25; PSQI score ≥5). The two groups were not significantly different in terms of age, gender, years of education, ethnicity, handedness, body mass index, and cognitive performance. Compared to normal sleepers, poor sleepers exhibited much faster rates of volume loss, over threefold in the right hippocampus and fivefold in the right posterior cingulate over 2 years. In contrast, there were no significant differences in the rates of volume loss in the cerebral and cerebellar grey and white matter between the two groups. Rates of volume loss in the right posterior cingulate were negatively associated with global PSQI scores. Poor sleep significantly accelerates volume loss in the right hippocampus and the right posterior cingulate cortex. These findings demonstrate that self‐reported sleep quality explains inter‐individual differences in the rates of volume loss in cognitively‐critical brain regions in healthy older adults and provide a strong impetus to offer sleep interventions to cognitively normal older adults who are poor sleepers.